Gut microflora: association and risk of sigmoid colon and rectal cancer - Mohamed Sikandar, Faizah (2015)
BACKGROUND: Based on published data that few bacterial species (normal flora) of the Gastrointestinal (GI) tract can promote carcinogenesis of the large bowel, a study was carried out to identify types of bacteria that present in tumour of the sigmoid colon and rectum in comparison with mucosa of the normal sigmoid colon and rectum and its association with the malignancy of the sigmoid colon and rectum. METHOD: Total of 66 patients, who presented with bowel symptoms, underwent colonoscopy procedures and was divided into two groups (normal and cancer group). Two biopsies were taken at the sigmoid colon and rectum (one biopsy each part) from 33 patients with normal colonoscopy results. One biopsy was taken from the tumour site, either at the sigmoid colon or rectum from the other 33 patients with positive colonoscopy findings. These biopsied samples were sent to the microbiology lab for cultivation and bacterial identification. RESULTS: More than 30 types of bacteria were isolated from the mucosa of the normal sigmoid colon and rectum with few differences in the species. The bacterial colonization appeared to be more in the rectum compared to the sigmoid colon. Proteus mirabilis, Beta haemolytic streptococcus, Enterococcus avium, Clostridium bifermentans, Morganella morganii, Streptococcus mutans, Parvimonas micra, Eggenthella lenta, Clostridium subterminale and Finegoldia magna are significantly associated with sigmoid colon carcinoma with (p<0.05). Proteus mirabilis and Morganella morgana were significantly associated with rectal carcinoma (p<0.05). CONCLUSION: Our study suggested that there is a difference in the type of bacterial species in different part of the bowel (between sigmoid colon and rectum) with more bacterial colonies in the rectum compared to sigmoid colon and there was an association of certain bacteria with an increased risk of developing carcinoma.